2019
DOI: 10.55279/jafmdc.v1i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Professional Quality of Life and Its Association with Work Experience and Income among Healthcare Worker

Abstract: Objective: The objective of the study is to assess job satisfaction between groups of healthcare workers based on their work experience and monthly salary.Methodology: Healthcare workers (n=81) including clinicians, nurses and medical teachers were recruited from a private medical institute at Lahore. Job Satisfaction Survey (JSS) and Professional Quality of Life (ProQOL) Scale including its component scales of Compassion Satisfaction (CS), Burnout (BO) and Secondary Traumatic Stress (STS) were used to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…According to our study, the mean PSS scores have declined with more years of experience and increased with fewer years of experience. These findings are consistent with the findings of a study by Maroof, which identified a similar scenario of Pakistani health care workers based on work experience [ 31 ]. In 2002, Newbury-Birch explained the reasons that fear of making mistakes and workload causes stress in dentists’ initial years of practice [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to our study, the mean PSS scores have declined with more years of experience and increased with fewer years of experience. These findings are consistent with the findings of a study by Maroof, which identified a similar scenario of Pakistani health care workers based on work experience [ 31 ]. In 2002, Newbury-Birch explained the reasons that fear of making mistakes and workload causes stress in dentists’ initial years of practice [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…High levels of compassion satisfaction and low levels of burnout and secondary traumatic stress result in With regard to the negative association between EDs-career duration and secondary traumatic stress, our results confirmed previous studies conducted among intensive care and oncology nursing units, 40 trauma nurses, 41 and healthcare workers including clinicians, nurses, and medical teachers. 42 A possible explanation may be that HCPs with lower EDs-career duration have not yet acquired professional tools relevant to the field of EDs, and as such they may be more vulnerable to complex situations that arise in caregiving for patients who are coping EDs. 43 Moreover, according to the Conservation of Resources (COR) theory, 44 professional career duration (ie, seniority) is included among the "condition" resources.…”
Section: Discussionmentioning
confidence: 99%